Effectiveness of Gastrografin in Resolving Small Bowel Obstruction (Medical Forum Monthly, 2024)
Objectives: To determine the effectiveness of Gastrografin in resolving intestinal obstruction.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted in the Department of Surgery, Shaikh Zayed Hospital, Lahore from 02-10-2013 to 02-04-2014.Materials and Methods: One hundred thirty five patients who having small bowel obstruction were admitted through out-patient, accident & emergency departments. Every participant was explained about both procedures and their consequences.Results: Average age was 44±70 years. 77 (57%) were males and 58 (43%) were females with a male to female ratio was 1.32:1. In 58 (43%) male patients the obstruction was resolved, but in 19 (14%) male patients obstruction was not resolved. In 41 (30%) female patients the obstruction was resolved and in 17 (12%) female patients the obstruction could not be resolved. Overall, in 99 (73%) patients, the obstruction was resolved but in 36 (27%) of patients the obstruction was not resolved.Conclusion: Gastrografin is a secure and reduces the need for surgery when conservative treatment fails. It remains a leading cause of hospital admission in surgical departments.